Melampaui Binaritas: Studi Filantropi Islam di Indonesia - Azami, Ahmad Fadli; Azca, Muhammad Najib (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2023)
The study of Indonesian Islamic philanthropy has so far been carried out by scholars with organizations and managerial governance as the locus. The existing studies do not provide enough articulation space for the dynamics of traditional philanthropy. This draws the author's attention to discursively look at the portrait of Islamic philanthropy in Indonesia by placing traditional and modern models more proportionally. The results are, first, Islamic philanthropy is based on religious doctrine. Second, modern and traditional philanthropy have different articulations. Modern philanthropy inevitably tries to adopt neoliberal values by referring to managerialistic, formalized governance for the humanitarian agenda. Meanwhile, traditional philanthropy is limited, interpersonal, based on the ethics of immediacy, and adheres to the justification of Godliness as the main thing, as in the case of Muludan. Third, the traditional and modern models have shown their respective achievements and challenges. Indonesian Islamic philanthropy tells the story of a philanthropic movement that is not singular, reflecting the contestation between Islamic teachings and neoliberal values.